Restoring Color Perception to the Blind: An Electrical Stimulation Strategy of Retina in Patients with End-stage Retinitis Pigmentosa - Yue, Lan; Castillo, Johnny; Gonzalez, Alejandra Calle; Neitz, Jay; Humayun, Mark S (Ophthalmology (Rochester, Minn.), 2021)
Bioelectronic retinal prostheses that stimulate the remaining inner retinal neurons, bypassing degenerated photoreceptors, have been demonstrated to restore some vision in patients blinded by retinitis pigmentosa (RP). These implants encode luminance of the visual scene into electrical stimulation, however, leaving out chromatic information. Yet color plays an important role in visual processing when it comes to recognizing objects and orienting to the environment, especially at low spatial resolution as generated by current retinal prostheses. In this study, we tested the feasibility of partially restoring color perception in blind RP patients, with the aim to provide chromatic information as an extra visual cue. Case series. Seven subjects blinded by advanced RP and monocularly fitted with an epiretinal prosthesis. Frequency-modulated electrical stimulation of retina was tested. Phosphene brightness was controlled by amplitude tuning, and color perception was acquired using the Red, Yellow, Green, and Blue (RYGB) hue and saturation scaling model. Brightness and color of the electrically elicited visual perception reported by the subjects. Within the tested parameter space, 5 of 7 subjects perceived chromatic colors along or nearby the blue-yellow axis in color space. Aggregate data obtained from 20 electrodes of the 5 subjects show that an increase of the stimulation frequency from 6 to 120 Hz shifted color perception toward blue/purple despite a significant inter-subject variation in the transition frequency. The correlation between frequency and blue-yellow perception exhibited a good level of consistency over time and spatially matched multi-color perception was possible with simultaneous stimulation of paired electrodes. No obvious correlation was found between blue sensations and array placement or status of visual impairment. These findings present a strategy for the generation and control of color perception along the blue-yellow axis in blind patients with RP by electrically stimulating the retina. It could transform the current prosthetic vision landscape by leading in a new direction beyond the efforts to improve the visual acuity. This study also offers new insights into the response of our visual system to electrical stimuli in the photoreceptor-less retina that warrant further mechanistic investigation.